PENGARUH PROMOSI DAN KEPERCAYAAN KONSUMEN TERHADAP KEPUTUSAN PEMBELIAN PADA PENGGUNA APLIKASI E-COMMERCE TOKOPEDIA - Andiani, Lidia; Riantama, Farrel; Andriansyah, Agussalim (Inspirasi Ekonomi : Jurnal Ekonomi Manajemen, 2023)
The purpose of this study was to test the Promotion (X1) and Consumer Trust (X2) variables on Purchase Decisions (Y) in the Tokopedia E-Commerce application in the Management student study program at STIE Malangkucecwara in the 2022/2023 academic year. The type of research used in this research is quantitative research with explanatory methods. The population of this study was 163 students with a sample of 62 students. The analytical method used in this study used the IBM SPSS Statistics 23 application. The results showed that the Promotion variable (X1) had a positive effect of 5,600 and the Consumer Trust Variable (X2) had a positive effect of 4,218. From the results of this study, it can be concluded that Promotion and Consumer Trust influence purchasing decisions.